Neuroprognostication in critical care - Greer, David M. 1966-; Dangayach, Neha S. 1983- (Cambridge medicine (Series), 2024)
Neuroprognostication in patients with primary neurological diagnoses as well as in critically ill patients with concomitant neurological diagnoses is increasingly complex. With advances in critical care, the focus of the field is progressively moving from survivorship to improving patients' quality of life. This evidence-based resource provides an in-depth analysis of different aspects of prognostication in neurologically critically ill patients, covering how to gather the correct data and synthesize this information at the bedside. Delving into disease specific prognostication such as traumatic brain injury, acute ischemic stroke and delirium, guidance is provided for choosing management strategies based on overall perception of prognostication and shared decision making. Other topics covered include religious and legal issues, palliative care, chronic critical illness and new frontiers including machine learning and biomarkers usage. An online version of the book with expandable figures can be accessed on Cambridge Core, via the code printed inside the cover